1994
DOI: 10.1002/pola.1994.080321104
|View full text |Cite
|
Sign up to set email alerts
|

Novel polystyryl resins for size exclusion chromatography

Abstract: New size exclusion chromatography (SEC) resins based on a crosslinker having independent vinyl groups have been produced and compared with SEC resins based on divinylbenzene‐55 (DVB). 1,2‐Bis(p‐vinylphenyl)ethane (p,p‐BVPE) and its meta‐isomers were suspension‐copolymerized with p‐methylstyrene in the presence of different porogens to give particles of about 5 μm average diameter. The porous particles were slurry‐packed into stainless steel columns for SEC evaluation. Calibration curves were obtained using nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Li et al 27 recently reported the suspension copolymerization of p-methylstyrene with 1,2-bis(pvinylphenyl) ethane (and its m isomer); the vinyl sites of this crosslinker are deconjugated, unlike those of DVB. Spherical macroporous beads with a distinctive cauliflower surface texture were prepared, which compared very favorably with equivalent DVB-based resins as a packing material for size exclusion chromatography.…”
Section: Comments On Emulsion and Suspension Polymerization Techniquesmentioning
confidence: 97%
“…Li et al 27 recently reported the suspension copolymerization of p-methylstyrene with 1,2-bis(pvinylphenyl) ethane (and its m isomer); the vinyl sites of this crosslinker are deconjugated, unlike those of DVB. Spherical macroporous beads with a distinctive cauliflower surface texture were prepared, which compared very favorably with equivalent DVB-based resins as a packing material for size exclusion chromatography.…”
Section: Comments On Emulsion and Suspension Polymerization Techniquesmentioning
confidence: 97%
“…The protocol that can be found in the literature [41] was modified as follows: A mixture of 11.3 mL p-vinylbenzyl chloride (80 mmol) and 1.95 g magnesium (80 mmol) in 200 mL THF was gently stirred under argon at RT for 1.5 h. The rate of reaction was controlled by cooling with water or stirring. Afterwards, the mixture was extracted with a saturated NaCl solution.…”
Section: Monoliths Copolymerised From Methylstyrene and Bis(vinylphenmentioning
confidence: 99%
“…During the last two decades, the applications of the fine polymer particles have been gradually increasing in various fields, such as for electronic, biology, pharmacology, photographic industry, chromatography, controlled release reservoirs and chemical industry [1][2][3][4][5]. Recently, the possibility of utilization of heterocoagulation for the formation of polymer composite particles has been investigated by several groups [6][7][8] since it provides the possibility of better control for certain types of composite particle morphology.…”
Section: Introductionmentioning
confidence: 99%